The influence of СOVID-19 pandemic on the level of interpersonal of youth (Actual Problems of Psychology in Educational Institutions, 2022)
This article highlights the definition of interpersonalrelationships, their functions and influence on the activity of a personality.The role of communication and its importance are formulated, theproblem of interpersonal relationships among youth is disclosed, theissue of relationships within student groups in particular. With regardto the current everyday-life difficulties, the main goal of this article is toresearch СOVID-19 pandemic’s influence on the level of interpersonalrelationships among students before quarantine restrictions and after.Therefore, the empirical research among the students was held by themeans of questionnaire. This article presents and analyses the resultsof the experiment connected to the understanding of the СOVID-19pandemic’s influence on the level of interpersonal relationships of youth.